Structural Integrity Re-Use Assessment for Fixed Structures - Hla Myint, Kyaw Thiha (IRC, 2016)
In a time not far from now, there will be a significant increase in the decommissioning activities of fixed offshore platforms in Asia Pacific Region. The usual methods of decommissioning comprise the complete removal, partial removal, reefing or re-using of the offshore structure. The major challenges that encounter during the complete or partial removal decommissioning is the shortage of decommissioning yards for managing onshore disposal. Therefore, reefing or re-using of the structure has better aspect of sustainability rather than the complete removal and disposal method. Reusing of the old structure can be not only cost saving but also will much reduce the emission of carbon dioxide during the steel manufacturing process from iron ore. In this report, it will be focused on the jacket of the fixed offshore structure and there will be two parts to discuss; structural integrity assessment and structural analysis. Before the structure is being reused, a structural integrity assessment is carried out to determine the current integrity of the structure. Based on the integrity assessment, modifications and/ or refurbishing are made if there is any and structural analysis is carried out to assess the strength of the offshore structure for reuse purpose.